Immunohistochemical analysis of syndecan-1 in leukoplakia and oral submucous fibrosis - Sushant S Kamat; G S Kumar; Ajit V Koshy (Wolters Kluwer Medknow Publications, 2013)
Background: Syndecan-1 is abundant in normal tissues and reduced in squamous cell carcinomas. Leukoplakia and oral submucous fibrosis (OSF) are oral pre-cancerous disorders that have potential for malignant transformation. The aim of this study was to evaluate the expression of syndecan-1 in leukoplakia and OSF and to identify its role as a reliable marker for predicting malignant changes. Materials and Methods: Expression of syndecan-1 was examined immunohistochemically in 42 cases of oral leukoplakia with or without epithelial dysplasia, 28 cases of OSF and 10 cases of normal oral epithelia as control. Mann-Whiteny 'U' test was used for statistical analysis and the level of significance was fixed at P < 0.05. Results: Intense syndecan-1 expression was observed in nine cases with normal epithelium. Immunopositivity was lost gradually as the extent of epithelial dysplasia increased. The significant reduction in syndecan-1 expression was observed in leukoplakia as epithelial dysplasia progressed from moderate or severe. Similarly, significant reduction was observed in staining intensities in OSF with dysplasia. Conclusion: The results reveal that down-regulation of syndecan-1 expression is associated with dysplastic changes in leukoplakia and OSF. Thus syndecan-1 can be considered as marker for predicting malignant changes.